Peran Blater dalam Kehidupan Masyarakat Madura - Intan Ratnadilla (Mathematics Education Study Program, 2025)
In Madura there is a public mention of a figure known as a blater. In the life of Madurese, blater is synonymous with negative things. This is because blater has a culture of violence in solving problems. In solving the problem, the blater performs an action called carok. Carok is used as an arena of legitimacy to strengthen one's social status as a blater. Blater identity refers to the brave, arrogant and courageous nature of a person by resorting to violence when solving a problem. Nevertheless, in his life blater has a positive side to society. Many people need blater assistance for various purposes. therefore, this study seeks to explore how the positive side of blater in the life of Madurese. This research uses descriptive qualitative research methods with a sociological approach The sociological approach is used to trace a social phenomenon that occurs in people's lives. By using a sociological approach, researchers can trace the figure of Blater whose daily life is identical to violence in Madura. As for collecting data, researchers use literature study techniques and interviews.